A Comprehensive Perspective of Strindberg’s Impact in the Development of Modern Drama - Yasir Dhain, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
This study is distinctively restricted to the perspective of Strindberg’s impact in modern drama because he is one of the most important dramatists in modern drama and modern theatre. He distinguishes himself as a great playwright from his contemporaries and the others in his miserable life and creative skill in writing the literary texts. The study aims to shed light on Strindberg’s impact in the development of modern drama and his influence on some famous dramatists in the modern age, such as Shaw, Ibsen, and others. It also shows Strindberg’s belief in the continuous war between men and women. It is divided into eight sections, each analyzing a topic. Finally, the study has reached some conclusions that verify the hypothesis of the study.